Self-help and health in Europe : new approaches in health care - Hatch, Stephen; Kickbusch, Ilona, 1950-; World health organization. Regional office for Europe Copenhagen (Copenhagen : WHO Regional Office for Europe ; Albany, N.Y. : WHO Publications Centre [distributor], 1983)
Hoe zit het met zelfhulpgroepen in de praktijk: we denken hierbij bijvoorbeeld aan de anonieme alcoholiekers.
Includes bibliographies.
Keywords: Medical care -- Europe; Self-care, Health -- Europe; Self-help groups -- Europe